Gas chromatography/mass spectrometry measurement of xenon in gas‐loaded liposomes for neuroprotective applications. (28th November 2016) - Klegerman, Melvin E.; Moody, Melanie R.; Hurling, Jermaine R.; Peng, Tao; Huang, Shao‐Ling; McPherson, David D.
Abstract : Rationale: We have produced a liposomal formulation of xenon (Xe‐ELIP) as a neuroprotectant for inhibition of brain damage in stroke patients. This mandates development of a reliable assay to measure the amount of dissolved xenon released from Xe‐ELIP in water and blood samples. Methods: Gas chromatography/mass spectrometry (GC/MS) was used to quantify xenon gas released into the headspace of vials containing Xe‐ELIP samples in water or blood. In order to determine blood concentration of xenon in vivo after Xe‐ELIP administration, 6 mg of Xe‐ELIP lipid was infused intravenously into rats. Blood samples were drawn directly from a catheterized right carotid artery. After introduction of the samples, each vial was allowed to equilibrate to 37°C in a water bath, followed by 20 minutes of sonication prior to headspace sampling. Xenon concentrations were calculated from a gas dose–response curve and normalized using the published xenon water–gas solubility coefficient. Results: The mean corrected percent of xenon from Xe‐ELIP released into water was 3.87 ± 0.56% (SD, n = 8), corresponding to 19.3 ± 2.8 μL/mg lipid, which is consistent with previous independent Xe‐ELIP measurements. The corresponding xenon content of Xe‐ELIP in rat blood was 23.38 ± 7.36 μL/mg lipid ( n = 8). Mean rat blood xenon concentration after intravenous administration of Xe‐ELIP was 14 ± 10 μM, which is approximately 15% of the estimated neuroprotective level. Conclusions: Using this approach, we have established a reproducible method for measuring dissolved xenon in fluids. These measurements have established that neuroprotective effects can be elicited by less than 20% of the calculated neuroprotective xenon blood concentration. More work will have to be done to establish the protective xenon pharmacokinetic range. Copyright © 2016 John Wiley & Sons, Ltd.